A framework for assessing the effectiveness of USAID's food security programme in a developing country. Issue 3 (2nd April 2020) - Dzigbede, Komla D.
ABSTRACT: This article presents a simple framework for gauging the effectiveness of an international development agency food security programme in a small developing country. It focuses on the United States Agency for International Development's (USAID) Feed the Future programme and uses Ghana as a case study. The article develops a basic regression discontinuity model of food security outcomes and tests the model using simulated data on food availability, access, and utilisation in Ghana. Results show positive programme outcomes for crop yield, production value, and dietary diversity among smallholder farmer households. The evaluation framework may be useful as a preliminary test and leading indicator of country programme effectiveness.